PENGEMBANGAN APLIKASI PERHITUNGAN SUARA SISTEM SAINTE LAGUE PADA PEMILU 2019 BERBASIS ANDROID - Achmad Zaki Yamani (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
General Elections is one form of embodiment of democratic system applied in Indonesia. Election is the process of selecting people's representatives who will occupy certain positions which one of them is the election of legislative members. Referring to Law No. 7 of 2017 on General Election, this study aims to find out the vote counting process of legislative elections by the method of Sainte Lague applied into an application. The method applies the divisor's calculation not to the seat quotas, but to the vote which will be divided by the odd number (1,3,5,7) for the order of each seat. With this application the process of inputting the results of the calculation of the voice while can be done directly using mobile-based applications. The process of storing data from application users to database servers using a relatively lightweight firebase. With the draft of this application, the presentation of recapitulation data of the result of the temporary vote of the official election can be conducted without having to wait for the official announcement of the Central KPU. In addition, this application will make it easier to see the results of real recapitulation in the form of text and the sequence of the largest seat acquisition. The presentation of the recapitulation result stems from the political party vote acquisition data in each region.